Sialylated galacto-oligosaccharides and 2′-fucosyllactose reduce necrotising enterocolitis in neonatal rats. Issue 2 (23rd May 2016) - Autran, Chloe A.; Schoterman, Margriet H. C.; Jantscher-Krenn, Evelyn; Kamerling, Johannis P.; Bode, Lars
Abstract: Necrotising enterocolitis (NEC) is one of the most frequent and fatal intestinal disorders in preterm infants and has very limited treatment options. Breast-fed infants are at a 6–10-fold lower NEC risk than formula-fed infants, and we have previously shown that human milk oligosaccharides (HMO) improved survival and reduced pathology in a rat NEC model. The HMO disialyllacto- N -tetraose (DSLNT) was most effective, and sialylation was shown to be essential for its protective effect. Galacto-oligosaccharides (GOS), currently added to some infant formula, but not containing sialic acid, had no effect. In addition to DSLNT, our previous work also showed that the neutral HMO fraction, which contains high concentrations of 2′-fucosyllactose (2′FL), slightly improved pathology scores. Here, we assessed the in vivo efficacy of 2′FL, as well as of GOS that we enzymatically sialylated (Sia-GOS). Neonatal rats were randomised into the following study groups – dam-fed (DF), formula-fed (FF), FF containing pooled HMO (10 mg/ml), GOS (8 mg/ml), Sia-GOS (500 µm ) or 2′FL (2 mg/ml) – and subjected to the established NEC protocol. The DF and HMO groups had the lowest pathology scores with mean values of 0·67 (sd 0·34) and 0·90 (sd 0·47), respectively. The FF group had significantly elevated pathology scores of 2·02 (sd 0·63). Although the addition of GOS to the formula had no protective effect and generated scores of 2·00 (sd 0·63), the addition of Sia-GOS or 2′FL significantly lowered pathology scores to 1·32 (sd 0·56) ( P <0·0034) and 1·43 (sd 0·51) ( P <0·0040), respectively. The results warrant further studies to investigate the underlying mechanisms and to assess safety and efficacy in human neonates.